Adverse Events in Cells, Tissues, and Organs Donation and Transplantation - Schuantes Paim, Sibele Maria; Roza, Bartira de Aguiar; Schirmer, Janine (Brazilian Journal of Transplantation, 2022)
Objective: To characterize adverse events in cells, tissue, and organs donation, and transplantation notified in the state of São Paulo, Brazil. Method: Descriptive study with quantitative approach. Data provided by Transplantation Central of São Paulo from the “Individual notification form of adverse reactions in Biovigilance”, of the FormSUS platform, between 2016 and 2019, and categorized according to the nomenclature recommended by the World Health Organization regarding nature and type of event, severity, and imputability. Analysis was performed using descriptive statistics. Results: Fifty-two notifications were characterized, 90.4% related to the recipient, 78.8% from allogeneic procedures, 48.2% related to organs, and 44.2% to hematopoietic stem cells. The causes of notifications were infections (55.7%), other ones (30.8%), and neoplasms (13.5%). Most of the events were moderate (44.3%), and 36.5% were confirmed. Conclusion: It was possible to identify the scenario of biovigilance in the state, visualizing that the main adverse events are related to the receptor from allogeneic procedures. In addition, the major cause of adverse events in the state of São Paulo are infections, especially those caused by Mycobacterium tuberculosis and Klebsiella pneumoniae. The characterization of these events can support the development of safety strategies to prevent recurrence, the realization of institutional training and public policies to encourage notification and expand the understanding of adverse events in this scenario, since it is only possible to ensure quality and safety in health care, especially in the context of donations and transplants, from the recognition of reality